The effect of stimulus threat on experimentally induced secondary hyperalgesia - Bedwell, Gillian Jennifer (Division of Physiotherapy, 2020)
Background Neuropathic pain affects 7 – 10% of people and responds poorly to pharmacotherapy. Numbers needed to treat for first line drugs range from 4 – 8. Therefore, there is an obvious need for improved understanding of the mechanisms of neuropathic pain to inform improved treatments. Mechanistic research on neuropathic pain frequently uses a human surrogate model of secondary hyperalgesia that is a common feature of neuropathic pain. The value of experimentally inducing secondary hyperalgesia is that one can then test the influence of different pharmacological and nonpharmacological interventions. This may shed some light on the physiological mechanisms within the spinal cord, which possibly also translates to the effects of the interventions on other pathways that are involved in processing signals that may be related to pain. Additionally, pain is known to be influenced by the threat value of the situation. Many South Africans live under constant threat: less than a third of South Africans feel safe walking alone at night. This constant threat may be perpetuating the pain problem in South Arica. However, the mechanism by which threat achieves this influence on pain is unclear. This project is focused on one possible mechanistic hypothesis: that threat influences pain by affecting central physiological changes within the dorsal horn of the spinal cord. These central changes often present clinically as secondary hyperalgesia. A thorough understanding of these mechanisms will inform improved treatment strategies. Methods Phase one: systematic review and meta-analysis The aim of this systematic review was to identify, describe, and compare methods that have been used to manipulate experimentally induced secondary hyperalgesia in healthy humans. A systematic search strategy (conducted on 01 October 2019) was supplemented by reference list checks and direct contact with identified laboratories to maximise the identification of data reporting the experimental manipulation of experimentally induced secondary hyperalgesia in humans. Studies were only included if they were published and in-press or accepted records for which the title, abstract, and full-text versions were available in English. Duplicate screening, risk of bias assessment, and data extraction procedures were used. Risk of bias was appraised for the following domains: selection, performance, detection, attrition, measurement, reporting, and other sources of bias. Data were extracted using a standardised data extraction form. This form was piloted and refined beforehand. Authors were asked to provide data were necessary. Data were pooled by method of v manipulation and outcome (intensity of secondary hyperalgesia, area of secondary hyperalgesia, or both). Phase two: experimental paradigm An experimental study was developed and conducted to investigate the effect of a stimulus threat on secondary hyperalgesia. The aim of this study was to investigate the effect of a manipulation of the threat value of a stimulus on experimentally induced secondary hyperalgesia in healthy human volunteers. All participants underwent a sham skin examination (the threat stimulus) at both the experimental and control sites. Through this sham skin examination, participants were informed that their skin integrity was fragile at the experimental site and robust at the control site. Secondary hyperalgesia was induced with high-frequency electrical stimulation at both the experimental and control site. Sensory testing was conducted at the experimental and control site, providing a withinsubject comparison of the intensity and area of secondary hyperalgesia at each site. It was hypothesised that greater threat will be associated with (hypothesis 1) greater intensity and (hypothesis 2) greater surface area of induced secondary hyperalgesia. Results Phase one: systematic review Twenty-one studies with non-pharmacological manipulations were included. Nine (out of 21) studies assessed intensity of secondary hyperalgesia after manipulation. Nicotine deprivation and negative expectations about the induction increased the intensity of secondary hyperalgesia. Three studies using attentional modulation and cognitive loading reported conflicting results with two studies having no effect and the other reporting a decrease in the intensity of secondary hyperalgesia. Emotional disclosure decreased the intensity of secondary hyperalgesia at four days and at one month after the manipulation. Hot/cold application, and verbal suggestion had no effect on the intensity of secondary hyperalgesia. Seventeen (out of 21) studies assessed area of secondary hyperalgesia after manipulation. Nicotine deprivation and sleep deprivation increased the area of secondary hyperalgesia. Hyperbaric oxygen therapy, cognitive behavioural therapy, emotional disclosure, spinal manipulation, transcranial direct current stimulation, and placebo analgesia decreased the area of secondary hyperalgesia. Interestingly, the effects of emotional disclosure and hyperbaric oxygen therapy were evident one month after manipulation. Acupuncture had no significant effect on the area of secondary hyperalgesia. Four studies assessed the effect of hot/cold application. Three studies reported no effect and one study reported an increase in the area of secondary hyperalgesia after cold application.